Situation Report: Hungary, 7 September 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Dissidents Demonstrate in Support of Solidarity Opposition Members Appeal to Peace Marchers Gabor Demszky Sentenced Polish Children Fail to Appear for Summer Vacation in Hungary Does the Jesuit Order Still Have a Future in Hungary? Nyers Says Hungarian Economic Reform a Necessity Whit Makes an Enterprise Manager Run? Endeavors to Boost Privately Financed Apartments Magyars in the Countries Surrounding Hungary Ben Hur Shown for the First Time in a Socialist Country New Initiatives to Stop Chronic Shortage of Components